Prevention of Voice Phishing through Analysis of Telephone Call Voice Characteristic - Woo Park, Hyung; Bae Kim, Jong; Jin Bae, Myung (International Journal of Engineering and Technology, 2018)
Using a phone call to morale of others seeking money as voice phishing. When receiving these fraudulent calls are easily embarrassed, and if they get embarrassed, become more easily be cheated. These voice phishing techniques are evolving to be more intelligent and more diverse. Accordingly, the amount of damage and the victim reality is increasing. The phone call, only the minimum data necessary to transfer the information contained is passed to the other party through the wired or wireless communication networks. In the voice of phone call, It is because the communication system mainly conveys the voice and does not convey the facial expression, environmental situation, and psychological state of the other person. Therefore, it is difficult to judge the authenticity in speech of voice phishing over the telephone network, and it is easy to fall into the deceitful deceit of evolving fraud. In this paper, we analyze the characteristics of voice phishing voices, examine their characteristics, and use them to reduce fraud damage. The voices recorded by victims of actual telephone fraud were analyzed and the characteristics were summarized.Â Â